The effect of insulin, leptin, adiponectin, ghrelin levels in cord blood on growth in the first two years - Sema Tanrıverdi; Betül Ersoy; Fatma Taneli (Perinatal Medicine Foundation, 2022)
Objective: The main hormones and adipokines that regulate growth, energy metabolism and adipogenesis in the intrauterine period are insulin, leptin, ghrelin, and adiponectin. Changes in these hormones and adipokines may affect weight gain, obesity and metabolic syndrome in advanced ages. In this study, it was aimed to investigate the relationship between insulin, leptin, ghrelin, adiponectin levels in the cord blood of term newborns and growth in the first two years of age. Methods: Term newborns in our hospital between May 2019 and October 2019 were included in the study. Insulin, glucose, ghrelin, leptin and adiponectin levels were studied in the umbilical cord blood of 80 newborns. The growth of 44 of the 80 newborns included in the study was monitored until the age of two years. Results: The relationship between insulin, ghrelin, leptin and adiponectin levels in the cord blood of 44 newborns included in the study with growth up to two years of age was investigated. A positive correlation was found between the insulin level in the cord blood and birth weight, birth head circumference, and the weights at the 12th and 24th months of life. A negative correlation was found between the level of ghrelin in the cord blood and the weights at the 6th and 24th months of life. A positive correlation was found between the level of adiponectin in the cord blood and the weight in the 6th month of life. There was no significant correlation between cord leptin level and anthropometric measurements in the first two years of age. Conclusion: While the levels of insulin and adiponectin in the cord blood were positively correlated with the weight in the first two years of life, they were negatively correlated with the ghrelin level in the cord blood. The level of leptin in cord blood did not correlate significantly with the weight in the first two years of life.